Integrated Fishing Industry Zone Design Based on Capture Fisheries Potential in the Western–Southern Region of Aceh - Iing Pamungkas; Heri Tri Irawan (G-Tech: Jurnal Teknologi Terapan, 2026)
This research examines the potential of fishery resources, the feasibility of development, and the design of an Integrated Fisheries Industrial Zone (Kawasan Industri Perikanan Terintegrasi - KIPT) in the western-southern region of Aceh. This region possesses significant potential for capture fishery production, but the added value of fishery products remains low due to limitations in infrastructure and processing technology. The research method utilizes quantitative and qualitative analysis with the collection of primary and secondary data, evaluation of technical, economic, social, and environmental aspects, as well as the design of the Integrated Fisheries Industrial Zone. The research results indicate that the development of the KIPT in South Aceh is highly feasible from a technical and economic perspective, supported by adequate infrastructure, human resources, and regulations. Economic impact projections show an increase in added value of up to Rp2.1 trillion per year and job creation reaching 4,000-5,500 people. The KIPT design integrates modern and environmentally friendly facilities for ports, processing, cold storage, and logistics. The study recommends strengthening investment in infrastructure and human resource training to support the sustainability and competitiveness of the fisheries industry in Aceh.